Leachate Analysis of Heavy Metals in Cigarette Butts and Bricks Incorporated with Cigarette Butts - Kurmus, Halenur (Materials (Basel), 2020)
Billions of cigarette butts (CBs) are discarded as litter in the environment every year worldwide. As CBs have poor biodegradability, it can take several years for them to break down while leaching toxic chemicals and heavy metals. Mohajerani et al. (2016), based on long-term research, developed a method for the recycling of CBs in fired clay bricks with promising results. This paper presents and discusses the leaching behavior of potentially hazardous metals from used, unused, and shredded used CBs, and unfired and fired clay bricks incorporating CBs. The leachate analysis was conducted according to the Australian Bottle Leaching Procedure (ABLP) for pH values 2.9, 5.0, and 9.2. The aim was to quantify the amount of heavy metals leached, determine the relationship between the metal concentration leachate, pH of the solution and condition of the sample, and examine the effect of firing on the leaching capability of bricks. The leachate results were then compared to the concentration limits for heavy metals set by the United States Environmental Protection Authority (USEPA) national primary drinking water and the Environmental Protection Authority (EPA) solid industrial waste hazard categorization thresholds to assess the suitability of fired clay bricks incorporating CBs. Metals Cu, Zn, Mn, Al, Fe, Ti, and Ba demonstrated the highest leachate concentrations for pH 2.9 and pH 5.0 for used CBs. This suggests that used CBs are more prone to leaching heavy metals in areas with highly acidic rain compared to the natural range of precipitation. The leaching behavior of fired bricks incorporating CBs was considerably lower than that for the unfired bricks due to the immobilization of heavy metals during the firing process. However, the leaching of Cr and Ni was almost completely impeded after the firing of the bricks, and more than 50% of all the tested heavy metals were hindered.